'Mutiny on the Bounty': the genetic history of Norfolk Island reveals extreme gender-biased admixture. Issue 1 (December 2015) - Benton, Miles; Stuart, Shani; Bellis, Claire; Macartney-Coxson, Donia; Eccles, David; Curran, Joanne; Chambers, Geoff; Blangero, John; Lea, Rod; Griffiths, Lyn
Abstract Background The Pacific Oceania region was one of the last regions of the world to be settled via human migration. Here we outline a settlement of this region that has given rise to a uniquely admixed population. The current Norfolk Island population has arisen from a small number of founders with mixed Caucasian and Polynesian ancestry, descendants of a famous historical event. The 'Mutiny on the Bounty' has been told in history books, songs and the big screen, but recently this story can be portrayed through comprehensive molecular genetics. Written history details betrayal and murder leading to the founding of Pitcairn Island by European mutineers and the Polynesian women who left Tahiti with them. Investigation of detailed genealogical records supports historical accounts. Findings Using genetics, we show distinct maternal Polynesian mitochondrial lineages in the present day population, as well as a European centric Y-chromosome phylogeny. These results comprehensively characterise the unique gender-biased admixture of this genetic isolate and further support the historical records relating to Norfolk Island. Conclusions Our results significantly refine previous population genetic studies investigating Polynesian versus Caucasian diversity in the Norfolk Island population and add information that is beneficial to future disease and gene mapping studies.